Post–Liver Transplant Early Allograft Dysfunction Modifies the Effect of Pre–Liver Transplant Renal Dysfunction on Post–Liver Transplant Survival. Issue 9 (21st July 2021) - Wadei, Hani M.; Keaveny, Andrew P.; Taner, C. Burcin; Yang, Liu; Mai, Martin L.; Hodge, David O.; White, Launia J.; Mao, Shennen A.; Jarmi, Tambi; Croome, Kristopher P.
Abstract : Pre–liver transplantation (LT) renal dysfunction is associated with poor post‐LT survival. We studied whether early allograft dysfunction (EAD) modifies this association. Data on 2, 856 primary LT recipients who received a transplant between 1998 and 2018 were retrospectively reviewed. Patients who died within the first post‐LT week or received multiorgan transplants and previous LT recipients were excluded. EAD was defined as (1) total bilirubin ≥ 10 mg/dL on postoperative day (POD) 7, (2) international normalized ratio ≥1.6 on POD 7, and/or (3) alanine aminotransferase or aspartate aminotransferase ≥2000 IU/mL in the first postoperative week. Pre‐LT renal dysfunction was defined as serum creatinine >1.5 mg/dL or on renal replacement therapy at LT. Patients were divided into 4 groups according to pre‐LT renal dysfunction and post‐LT EAD development. Recipients who had both pre‐LT renal dysfunction and post‐LT EAD had the worst unadjusted 1‐year, 3‐year, and 5‐year post‐LT patient and graft survival, whereas patients who had neither renal dysfunction nor EAD had the best survival ( P < 0.001). After adjusting for multiple factors, the risk of death was significantly higher only in those with both pre‐LT renal dysfunction and post‐LT EAD (adjusted hazard ratio [aHR], 2.19; 95% confidence interval [CI], 1.58‐3.03; P < 0.001), whereas those with renal dysfunction and no EAD had a comparable risk of death to those with normal kidney function at LT (aHR, 1.12; 95% CI, 0.86‐1.45; P = 0.41). Results remained unchanged when pre‐LT renal dysfunction was redefined using different glomerular filtration rate cutoffs. Pre‐LT renal dysfunction negatively impacts post‐LT survival only in patients who develop EAD. Livers at higher risk of post‐LT EAD should be used with caution in recipients with pre‐LT renal dysfunction.